“Análisis de las características del ajuste curricular 2016 en el proceso pedagógico de la unidad educativa” Provincia de Cotopaxi”, periodo septiembre 2022- julio 2023”. - Ilaquize Troya, Sandy Pamela (2023)
Nowdays, several educational centers has affected the application of the 2016 curricular adjustment, this due to factors such as the health and social crisis experienced within the country, It has meant a setback in terms of curricular matter. For this reason, this present research proposes to highlight the importance of advancing with the pedagogical process according to the 2016 curricular adjustment, since it lies in providing a guide that students should develop, skills with performance criteria, indicators of achievement, curricular blocks the same that contributes to the integral development. Therefore, it is presented as a problem, how the 2016 curricular adjustment affects the pedagogical process in accordance with the reality that the teaching activities are carried out. Due to this, the objective of the present investigation lies in, to analyze the strengths and weaknesses in the application of the pedagogical models and the curricular adjustment 2016 through, of the observation in this project used the methodology with an interpretative approach, a qualitative investigation together with the field investigation, with the inductive method, through the techniques of observation and interview, for this, the interview and an observation guide applied to 35 students, a teacher and a director of the institution. To conclude, the provisions of the 2016 curricular adjustment are not met, due to multiple factors, the most prominent being the health emergency that the world suffered for approximately two years from 2020 to 2022.